Development of Science Literacy Test Instruments on Temperature and Heat Materials by Integrating Local Wisdom in the Production of Karang Batik, a Speciality of Tuban Regency - Muizzah, Novy Ainul; Jauhariyah, Mukhayyarotin Niswati Rodliyatul (Jurnal Pijar Mipa, 2025)
The local wisdom of Karang Batik from Tuban can provide a contextual basis for developing scientific literacy test instruments that are more meaningful. This study aims to develop a science literacy test instrument integrated with the local wisdom of Karang Batik making, which is unique to Tuban, and to identify students' science literacy profiles on the subject of temperature and heat. The development was carried out using the ADDIE model with data collection through interviews, validation questionnaires, and tests. Data analysis included content validity (Aiken's V and Percentage of Agreement), empirical validity (item–total correlation), reliability (Cronbach's Alpha), difficulty level, and discriminating power. The instrument was tested on 30 university students and implemented for 70 students at Tuban 1 State Senior High School. The results showed that content validity was in the very good category (PoA ≥ 97%), 67% of the items were empirically valid, and reliability was 0.690, which is classified as high. The level of difficulty ranged from easy to moderate, with sufficient discrimination. Students' science literacy profiles varied from very low to very high, with the majority of students in the high category. These findings indicate that the developed instrument is suitable for measuring science literacy and contributes to contextual learning efforts based on local wisdom.